ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢æ±‰è¯ä¸“ä¸šå¦ç”Ÿ å¯¹ä»£è¯â€œäººå®¶â€ä¸Žâ€œåˆ«äººâ€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Khasanah, Yulia Eka; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPronoun is an important part in Mandarin grammar. ?Ren Jia? and ?Bie Ren? are include as pronoun of person. Can be seen from the word the meaning of the words and the usage , there are similarities and differences. Therefore, students who learn Mandarin in process learning of these two words often make mistakes in understanding which is can create a misuse the words. To find out how the mastery codition of student from Mandarin education study program of FKIP UNTAN toward the pronoun words which are ?Ren Jia? and ?Bie Ren? , the writer use research test method to know the mastery condition of students and analyze student difficulties toward those two words. The result shows that the mastery condition of students toward ?Bie Ren? is better than ?Ren Jia?. ?Bie Ren? the percentage is 68% and ?Ren Jia? only 59%. In the analysis of the type of difficulty, the writer found the students mastery is in ?Ren Jia? used for the first person pronouns and in ?Bie Ren? for use with ?Zi Ji?. Keywords: ?Ren Jia?    ?Bie Ren?   Understanding Condition